1995
DOI: 10.1007/bf00036367
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome bands in freshwater triclads

Abstract: Four species of Triclads belonging to three families, Dugesia polychroa and Dugesia mediterranea (Dugesiidae), Planaria torva (Planariidae) and Dendrocoelum lacteum (Dendrocoelidae) were studied for chromosome banding : C-banding for all the species, ASG banding for Dugesia polychroa and G-banding for Dugesia polychroa and Dugesia mediterranea . C-banding results for Dugesia lugubris-polychroa group suggest a high level of heterochromatin evolution in the group . Small bands strictly limited to the centromeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Many times, karyograms have been used as a powerful tool for species identification, among both planarians and mollusks [ 21 , 52 ]. We showed that when planarians are collected in the wild, it can be difficult to identify the species only on the basis of morphological features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many times, karyograms have been used as a powerful tool for species identification, among both planarians and mollusks [ 21 , 52 ]. We showed that when planarians are collected in the wild, it can be difficult to identify the species only on the basis of morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, planarian species identification relies on the anatomy of sexual reproductive organs [ 18 , 53 , 54 ], which leaves the cohort of asexual planarian species largely uncatalogued. A proper characterization of the karyotypes of both sexual and asexual species would facilitate the identification and cataloging of planarian species, while also providing a rich resource for the understanding of karyotype evolution [ 21 ]. Similarly, over the years, the Gastropoda class has been reorganized multiple times in subclasses and families, and new species have been integrated, but the lack of a unique and established method for species identification has created multiple incongruences [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation